Ethanol Extract Concentrations of Anredera cordifolia, Aloe vera and Centella asiatica L. Leaves as Staphylococcus aureus Growth Inhibitor - Kore, Joldi Yosua; Tobing, Joshua H. L. (Jurnal Biologi Tropis, 2025)
Excessive oil production, irritation, and bacterial infections, especially those produced by Staphylococcus aureus, are the main causes of acne, a common skin condition. The antibacterial qualities of a variety of therapeutic plants have long been utilized. This study aimed to evaluate the antibacterial effectiveness of ethanol extracts of Binahong (Anredera cordifolia), Aloe vera (Aloe vera), and Pegagan (Centella asiatica L.) leaves against the growth of Staphylococcus aureus. This research was a true experimental study using the Kirby-Bauer disk diffusion method. The ethanol concentrations used for extraction were 30%, 40%, and 50%, with meropenem as a comparison. The inhibition zones were measured after 24 hours of incubation at 37°C. The results showed that all extracts exhibited moderate antibacterial activity, with inhibition zones increasing along with higher extract concentrations. The highest mean inhibition zone was observed in Pegagan (8.9 mm), followed by Binahong (8.783 mm) and Aloe vera (8.26 mm). Statistical analysis showed that concentration (p = 0.005), day (p = 0.038), interaction between plant*day (p = 0.011), and plant*concentration*day (p = 0.001) have a significant effect on the inhibition zone diameter (p < 0.05). Meanwhile, plant (p = 0.244), interaction between plant*concentration (p = 0.380), and interaction between concentration*day (p = 0.342) show no significant differences in the inhibition zone diameter (p > 0.05). The conclusion is that there are differences in the inhibitory power of binahong, aloe vera, and pegagan plant extracts against Staphylococcus aureus bacteria used with 70% ethanol solvent.